2012
DOI: 10.1111/j.1365-2958.2012.08149.x
|View full text |Cite
|
Sign up to set email alerts
|

A complex LuxR–LuxI type quorum sensing network in a roseobacterial marine sponge symbiont activates flagellar motility and inhibits biofilm formation

Abstract: Summary Bacteria isolated from marine sponges, including the Silicibacter–Ruegeria (SR) subgroup of the Roseobacter clade, produce N‐acylhomoserine lactone (AHL) quorum sensing signal molecules. This study is the first detailed analysis of AHL quorum sensing in sponge‐associated bacteria, specifically Ruegeria sp. KLH11, from the sponge Mycale laxissima. Two pairs of luxR and luxI homologues and one solo luxI homologue were identified and designated ssaRI, ssbRI and sscI (sponge‐associated symbiont locus A, B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
91
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(93 citation statements)
references
References 72 publications
(130 reference statements)
2
91
0
Order By: Relevance
“…While roseobacters are known to produce long-chain AHLs with various degrees of oxidation and side-chain saturation (11,30,34,35,46), the full complement of AHLs synthesized by lineage members and the contribution of these chemical signals to roseobacter ecology are not yet known. Here we identified a novel AHL, 3OHC 12:1 -HSL, in Phaeobacter sp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While roseobacters are known to produce long-chain AHLs with various degrees of oxidation and side-chain saturation (11,30,34,35,46), the full complement of AHLs synthesized by lineage members and the contribution of these chemical signals to roseobacter ecology are not yet known. Here we identified a novel AHL, 3OHC 12:1 -HSL, in Phaeobacter sp.…”
Section: Discussionmentioning
confidence: 99%
“…Similar phenotypes have been reported in another roseobacter, Ruegeria sp. strain KLH11; it has been suggested that quorum sensing may control the lifestyle switch between the sessile (biofilm) and planktonic forms of that strain (35,60). An analogous cell-to-cell communication may be used to induce dispersion of Phaeobacter sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…are also known to possess multiple systems and signals ( Table 2). The QS signals modulating these QSS range from unsubstituted-to substituted-HSLs, as well as peptides (DKPs), quinolones, hormones [69,[94][95][96][97][98][99][100][101][102][103][104][105]. In Yersinia, luxI/R homologues are majorly regulated by substituted AHLs [106][107][108].…”
Section: Othersmentioning
confidence: 99%
“…Not all AHL synthases belong to the LuxI family proteins; AHLs can also be synthesized by LuxM-and AinS-type proteins (11). QS systems can regulate a variety of cellular processes that are beneficial to a bacterial community, such as motility, sporulation, production of virulence factors and secondary metabolites, plasmid transfer, and biofilm formation (11), and they can facilitate the colonization of desirable niches (13).Bacteria with AHL-QS systems have been isolated from marine sponges (for examples, see references 7 and 14), and signaling molecules able to activate AHL biosensors have been reported in sponge extracts (7,14,15); the chemical nature of most of these signaling compounds is currently unknown. Gardères et al (16) identified AHLs produced in vivo by symbionts of the Celtic Sea sponge Suberites domuncula; more recently, it was determined that the signal molecule produced, N-3-oxododecanoyl-L-homoserine lactone, affects the expression of immune and apoptotic genes of the host sponge S. domuncula, possibly enabling the …”
mentioning
confidence: 99%